In-built resonant structures for precision assembly of X-Ray Optics for 4th Generation Light Sources. Issue 1 (1st December 2022) - Bainbridge, E.; Griffiths, J.; Clunan, J.; Docker, P.
Abstract: As the Diamond Light Source embraces the move towards becoming a fourth generation light source it will require its optics to perform under increasingly demanding conditions. Foremost amongst these conditions will be the increasing powers they are subjected to and the reducing real estate they must perform in. With these new challenges comes the need for greater understanding of how optics are assembled and how consistently this activity is carried out. In this paper, the concept of using passive resonant structures as part of a precision assembly approach for such optics is introduced. Numerical simulation of a passive resonant device comprising tines which are compressed as clamping force is increased is presented, revealing a frequency shift from intermediately fastened to fully tightened. This approach has the potential to provide a robust, game changing improvement to the accuracy of assembly of X-ray optics and subsequently a significant improvement in their performance.